The role of TET2 protein and oxidised forms of 5-methylcytosine in brain tumours - Eleftheriou, Maria (2020)
DNA methylation (5-methylcytosine, 5mC) is the major epigenetic modification involved in transcriptional regulation. Ten-eleven translocation (TET) proteins can enzymatically oxidise 5mC producing 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC) and 5-carboxylcytosine (5caC). According to several reports, 5hmC levels are reduced in human tumours; however, the distribution and the exact biological role of TET-dependent oxidation to 5fC and 5caC in cancers is poorly studied.